Patient reported outcomes following proton pencil beam scanning vs. passive scatter/uniform scanning for localized prostate cancer: Secondary analysis of PCG 001-09. (May 2020) - Mishra, Mark V.; Khairnar, Rahul; Bentzen, Søren M.; Larson, Gary; Tsai, Henry; Sinesi, Christopher; Vargas, Carlos; Laramore, George; Rossi, Carl; Rosen, Lane; Sun, Kai; Hartsell, William
Highlights: Data comparing PROs with pencil beam and passive scattering are lacking. We performed a comparison of EPIC domain scores for prostate cancer patients. Results were sensitive to the methods used to compare PROs. Future studies are needed to prospectively compare PROs following protons. Abstract: Background: Although pencil beam scanning (PBS) is the most conformal method for proton beam therapy (PBT) delivery, it is unknown if outcomes differ compared to treatment with passive scatter/uniform scanning (PS/US). This analysis compares patient reported outcomes (PRO) following PBS and PS/US for prostate cancer (PC) in a prospective multicenter registry study. Methods: We evaluated PROs with the Expanded Prostate Cancer Index Composite (EPIC) instrument for men with localized PC enrolled in PCG 001-09 (NCT01255748). PROs were assessed at baseline and through 12 months of follow-up. We compared mean changes in EPIC scores, as well as the proportions of men experiencing a one- and two-fold minimally important difference (MID) in domain scores, between PBS and PS/US. Multivariate analyses (MVAs) were performed to further evaluate the association between proton modality and PRO changes. Results: Three-hundred-and-four men completed EPIC at baseline; 72 received PBS and 232 received PS/US. The average quality-of-life (QOL) declines from baseline through 12 months did not significantly differ between the two groups. The proportion of men reporting a 1-MID decline at 12 months for PBS and PS/US was 34.3% and 27.4%, respectively, for urinary QOL ( P = 0.27); 40. 1% and 40.9% for bowel QOL ( P = 0.36); and 30. 1% and 36.6% for sexual QOL ( P = 0.94). Corresponding 2-MID declines for PBS and PS/US were observed in 26.9% and 13.2% of men for urinary QOL ( P = 0.01), 35.3% and 29.1% for bowel QOL ( P = 0.33); and 16.4% and 18.1% for sexual QOL ( P = 0.76). The association between proton modality and 2-MID changes in urinary QOL at 12-months remained significant on MVA (P = 0.007). Conclusions: The results of this analysis show differences between PBS and PS/US with regards to two-fold MID changes in urinary function at 12 months, but no differences for average score declines over time. Future studies evaluating PRO measures between the two PBT modalities are warranted.